2000
DOI: 10.1046/j.1365-2133.2000.03593.x
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluoro-1,25-dihydroxyvitamin D3has markedly increased potency in inhibiting proliferation of cultured human keratinocytes compared with 1,25-dihydroxyvitamin D3

Abstract: The increased potency and the long-lasting effects of F6-1,25(OH)2D3 suggest that F6-1,25(OH)2D3 may be a potent candidate agent for treating psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In addition, 1,25(OH) 2 D3, acting through the VDR, inhibits cell proliferation both in normal and malignant cells. 112115 Similarly, newly discovered vitamin D derivatives, such as 20(OH)D3, 20(OH)D2, 1,20 (OH) 2 D3, and 20,23(OH) 2 D3, show VDR-mediated antiproliferative properties comparable to those of 1,25(OH) 2 D3, 39,41,116120 while, at the same time showing less calcemic effects 39,54,117 …”
Section: Vitamin D In a ‘Nutshell’mentioning
confidence: 98%
“…In addition, 1,25(OH) 2 D3, acting through the VDR, inhibits cell proliferation both in normal and malignant cells. 112115 Similarly, newly discovered vitamin D derivatives, such as 20(OH)D3, 20(OH)D2, 1,20 (OH) 2 D3, and 20,23(OH) 2 D3, show VDR-mediated antiproliferative properties comparable to those of 1,25(OH) 2 D3, 39,41,116120 while, at the same time showing less calcemic effects 39,54,117 …”
Section: Vitamin D In a ‘Nutshell’mentioning
confidence: 98%
“…The cells were incubated in the presence of either 1,25(OH)2D3 or DG at 10 −6 M or placebo. Cellular proliferation was measured by incubation with [ 3 H]thymidine for 2 h as previously described [29]. After the 2-h incubation, the cells were rinsed three times with ice-cold PBS and incubated in 5% percholoric acid on ice for 30 min.…”
Section: Cell Culturementioning
confidence: 99%
“…F 6 ‐1,25(OH) 2 D 3 is a novel fluorinated derivative of the natural active vitamin D 3 metabolite, 1α,25‐dihydroxyvitamin D 3 (calcitriol). Experimental studies have shown that F 6 ‐1,25(OH) 2 D 3 has markedly increased potency and longer‐lasting effect in inhibiting proliferation of cultured normal and psoriatic human keratinocytes compared with 1,25(OH) 2 D 3 17,26 . F 6 ‐1,25(OH) 2 D 3 is about 10 times more potent than 1,25(OH) 2 D 3 in exerting various biological effects 16,17 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for using F 6 ‐1,25(OH) 2 D 3 (Fig. 1) is based on the observation that it has increased biological potency 16 and a longer‐lasting effect in inhibiting proliferation of cultured normal and psoriatic keratinocytes compared with calcitriol 17 . This study was designed to evaluate the therapeutic efficacy of F 6 ‐1,25(OH) 2 D 3 in treating psoriasis, in conjunction with a thorough evaluation of its potential toxicity on calcium metabolism.…”
mentioning
confidence: 99%